Aplicacion del metodo de Ritz a funcionales relajados en mecanica de los solidos - Feijóo, Raul Antonino (1973)
The theory of the first variations of different type of functionals is presented in this work. The Weierstrass – Erdmann corner conditions are obtained for each one of these functionals. The classical theory of the Ritz Method is developed, but when dealing with convergende of the aproximated solutions and performance of the Ritz coefficients, the theory of operators in Hilbert spaces is introduced; this makes it possible to have the problem in an elegant, clear and compact form. The concept of "extended functionals", a systematic way of getting them, the application of the Ritz Method to these functionals as well as mapping and the subdivition of the application domain are analyzed in this investigation. Numerical results for torsion in bars are compareci with results obtained through some other methods and also· the exact solution.